2017
DOI: 10.1002/2017gl075951
|View full text |Cite
|
Sign up to set email alerts
|

Dual Isotope Measurements Reveal Zoning of Nitrate Processing in the Summer Changjiang (Yangtze) River Plume

Abstract: Riverine nitrogen input into the coastal zone has increased remarkably in recent decades. Yet its transformation and recycling within hydrodynamically active regions remains unclear. Using observations of nitrate concentration and dual isotopic composition across the Changjiang River plume within a three end-member mixing model, we found deviations between the observed and expected values for mixing alone, revealing the nonconservative behavior of nitrate. Using cross correlations between concentrations and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 56 publications
(83 reference statements)
4
17
0
Order By: Relevance
“…The NO 3 − concentrations of the sampling stations ranged from 18.9 to 120 μM (Figure 7B). The δ 15 N‐NO 3 − values varied from 6.1‰ to 6.5‰ in the Changjiang runoff (salinity < 0.14), in a range similar to that reported by Yan et al 37 From the estuary mouth to the outer plume of the Changjiang Diluted Water, the δ 15 N‐NO 3 − values increased from 6.7‰ to 15.3‰, which were also comparable with the historical records from Yan et al 37 High δ 15 N‐NO 3 − values were observed in the offshore saline water mainly due to biological assimilation by phytoplankton (CTD fluorescence: 5.9–11 μg L −1 ). The difference of the δ 15 N‐NO 3 − values in the estuary surface water showed that the nitrogen isotopic ratio could provide important information about the nitrate transformation process in the Changjiang Estuary, further indicating the validity of our method for both freshwater and seawater.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The NO 3 − concentrations of the sampling stations ranged from 18.9 to 120 μM (Figure 7B). The δ 15 N‐NO 3 − values varied from 6.1‰ to 6.5‰ in the Changjiang runoff (salinity < 0.14), in a range similar to that reported by Yan et al 37 From the estuary mouth to the outer plume of the Changjiang Diluted Water, the δ 15 N‐NO 3 − values increased from 6.7‰ to 15.3‰, which were also comparable with the historical records from Yan et al 37 High δ 15 N‐NO 3 − values were observed in the offshore saline water mainly due to biological assimilation by phytoplankton (CTD fluorescence: 5.9–11 μg L −1 ). The difference of the δ 15 N‐NO 3 − values in the estuary surface water showed that the nitrogen isotopic ratio could provide important information about the nitrate transformation process in the Changjiang Estuary, further indicating the validity of our method for both freshwater and seawater.…”
Section: Resultssupporting
confidence: 86%
“…In addition to the chemical reduction method, the denitrifier method is also widely applied in the determination of δ 15 N‐NO 3 − values in water samples 37–39 . Specifically, the δ 15 N‐NO 3 − values of the laboratory KNO 3 standard were 0.67 ± 0.14‰ and 0.66 ± 0.20‰ using the Cd‐Cu column–NH 2 OH method and the denitrifier method (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The C offset and δ offset values combined with rates of oxidation and uptake allowed us to further unravel the dynamics of N species in the JRE. A similar offset method has been successfully applied to assess N dynamics in large estuaries and plumes, such as the Pearl River plume (Han et al, 2012) and the Yangtze River plume (Yan et al, 2017 (Table 3). In the upper estuary (Station J4), R AO was as high as 20.4 μmol L −1 day −1 , which was twentyfold higher than R NO (1.0 μmol L −1 day −1 ).…”
Section: Shifted N Transformation Processes Downstreammentioning
confidence: 99%
“…Supplementary information provided by N isotope (δ 15 N) investigations in the Loire estuary have nicely demonstrated the limitations inherited in the classical two end-member mixing approach (Middelburg & Nieuwenhuize, 2001). The δ 15 N provided specific aid in identifying N sources (Altabet, 2006;Wells et al, 2016;Yan et al, 2017), because δ 15 N from different sources may have distinct isotopic compositions (Altabet, 2006;Casciotti, 2016aCasciotti, , 2016b. Moreover, N biological cycling often changes isotopic compositions in predictable and recognizable directions (Casciotti, 2016b;Sigman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, stable isotope fractions, e.g., δ 15 N-NO − 3 , δ 18 O-NO − 3 , and δ 15 N-PN (particle nitrogen), have been introduced to trace DIN transport and transformation processes (Middelburg and Nieuwenhuize, 2001). The stable isotope technique has been applied in a number of estuaries located in temperate and sub-tropical zones, such as the Changjiang estuary (China; Yu et al, 2015;Yan et al, 2017), the Seine River estuary (France; Sebilo et al, 2006), the Thames estuary (UK; Middelburg and Nieuwenhuize, 2001) and the Werribee River estuary (Australia; Wong et al, 2014). The delineated reaction pathways and DIN sources/sinks from these research outcomes largely improved our understanding of the DIN cycle, which is crucial for projections as well as the regulation and enactment of laws.…”
Section: Introductionmentioning
confidence: 99%